NMDAR-ANTIBODY ENCEPHALITIS CAN BE ASSOCIATED WITH LATENT AUTOIMMUNE DISEASE. (29th November 2012) - Harding, K; Johnston, JA; Ali, K; Pearson, O; Pickersgill, TP
Abstract : In recent years N-methyl-D-aspartate receptor (NMDAR)-antibody encephalitis has been recognised as a distinct antibody-mediated disorder. We have previously described the case of NMDAR-antibody encephalitis associated with later development of Multiple Sclerosis. We present a second case of a young woman who first presented in 1983 with psychosis, behavioural change, abnormal limb posturing and seizures. EEG showed slow waves. CT head was normal. CSF was initially unremarkable. Anti-nuclear antibodies were negative. Her symptoms responded well to prolonged oral steroids and the diagnosis was made of antibody-negative cerebral lupus. In 1986 her symptoms recurred, and at this point CSF showed a mild pleocytosis of 8. She was again treated with steroids and ultimately recovered well though continued to be treated with antipsychotic medication long term. She was reviewed in 2010 at which point she had been neurologically stable for over two decades. Neurological examination was unremarkable. MRI revealed two periventricular lesions. ANA was now positive at 1:1280 and ds-DNA antibodies positive at 36. She had previously had two miscarriages and three normal pregnancies. She had arthralgia but no rash or photosensitivity. In addition, NMDAR antibodies were positive. We postulate that the initial episode in the 1980s was suggestive of NMDAR-antibody encephalitis. These two cases associated with a subsequent and very delayed autoimmune disease suggest that this condition may herald the fact of an underlying autoimmune tendency. It may be advisable to monitor such patients lifelong.